Syntheses of a Hyperbranched Polymer and Its Performance on Enhanced Oil Recovery - Qiao, Sanyuan; Liu, Qingwang; Zhang, Xian; Che, Hongchang (Frontiers in Chemistry, 2021)
A hyperbranched carboxylate-type polymer was synthesized through esterification and carboxymethylation, and its performance on enhanced oil recovery was experimentally evaluated. The optimum condition for esterification was 8 h at 120°C, where 3% PTSA as the catalyst and 9:1 mol ratio of the AB2 intermediate and trimethylolpropane were used. The optimum condition for carboxymethylation was 4 h at 80°C. The critical micelle concentration of the hyperbranched polymer was 433.63 mg/L, the Krafft point was 5°C, and the surface tension was lowered to 28 mN/m. In the range of 400–500 mg/L concentration, the adsorption onto the oil sand surface achieved equilibrium, and micellar solubilization reached 600 ml/mol. The interfacial tension can be lowered to a level of 10−2 mN/m by the single use of the hyperbranched polymer, and the value further decreased to a level of 10−3 mN/m while being formulated with sodium dodecylsulfate or NaOH. Oil recovery of water flooding was further enhanced by the single use of a hyperbranched polymer or the combination of hyperbranched polymer/sodium dodecylsulfate. The latter exhibited more prosperous advantages in low-permeability reservoirs.